Running Scared? A Critical Analysis of LGBTQ+ Inclusion Policy in Schools - Glazzard, Jonathan; Stones, Samuel (Frontiers in Sociology, 2021)
This article provides an overview of the UK government policy in relation to relationships and sex education in schools. It focuses on the latest statutory guidance which requires primary and secondary schools in England to teach pupils about different types of relationships, including same-sex relationships. We outline the current policy frameworks and present a rationale for why Lesbian, Gay, Bisexual, Trans and Queer (LGBTQ+) identities and relationships should be in the curriculum. We critically interrogate the government response and we present a framework to support the implementation of a whole school approach to LGBTQ+ inclusion. We draw on Meyer’s model of minority stress to explore risks to children and young people if they are not provided with an LGBTQ+ curriculum.